Adoptive cellular immunotherapy combined with chemotherapy versus chemotherapy alone in Chinese patients with metastatic colorectal cancer: a cost-effectiveness analysis to inform drug pricing - Huo, Liman; Liang, Ping; Duan, Yangyang; Xu, Yanmei; Tang, Jianhua; Lv, Qi; Feng, Rui (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the cost-effectiveness of adoptive cellular immunotherapy (ACI) combined with chemotherapy versus chemotherapy alone in Chinese patients with metastatic colorectal cancer (mCRC) and provide evidence-based support for drug pricing strategies.MethodsA Markov model was constructed using data from the NCT03950154 phase III clinical trial, which randomized 202 patients into two groups: ACI combined with oxaliplatin/capecitabine/bevacizumab (n=100) and chemotherapy alone (n=102). Clinical outcomes, including progression-free survival (PFS), overall survival (OS), and adverse events, were analyzed. Costs, quality-adjusted life-year (QALY), and incremental cost-effectiveness ratio (ICER) were calculated from the perspective of the Chinese healthcare system. Probabilistic sensitivity analysis was employed to assess model stability, accompanied by scenario analysis, with price simulations conducted under three willingness-to-pay (WTP) thresholds (1.5×, 1.94×, and 3× China’s per capita gross domestic product [GDP]).ResultsThe ACI group demonstrated superior clinical outcomes compared to chemotherapy alone, with a median PFS of 14.8 vs. 9.9 months (hazard ratio [HR]=0.60, p=0.009) and a median OS not reached vs. 25.6 months (HR=0.57, p=0.043). Over a 20-year simulation, the ACI group provided an additional 1.72 QALY, yielding an ICER of $35,881.71/QALY. At the base-case price ($6,819.45 per cycle), ACI remained cost-effective within China’s WTP threshold ($36,721.86/QALY). Scenario analysis revealed that extending the simulation time horizon to 10 and 15 years reduced the ICER to $40,804.77/QALY and $37,770.23/QALY, respectively. Systematic cross-validation of 2,448 model combinations (72 control group/34 ACI group survival curves) indicated that 71.84% of scenarios met predefined cost-effectiveness criteria (ICER range: $22,204 – $58,360/QALY). Price sensitivity analysis further demonstrated that cost-effectiveness advantages persisted when ACI cycle costs were reduced to $1,670.33 (corresponding to WTP=1.5×GDP=$18,360.93), $3,271.06 (corresponding to WTP = 1.94×GDP = $23,746.80), and $7,098.9 (corresponding to WTP = 3×GDP = $36,721.86).ConclusionAt current pricing, ACI combined with chemotherapy provides significant clinical and economic benefits for Chinese mCRC patients, with cost-effectiveness validated through multidimensional scenario analyses and model evaluations. Further evidence is required to validate and refine the findings.